2017
DOI: 10.1530/jme-16-0196
|View full text |Cite
|
Sign up to set email alerts
|

Impaired adipose expansion caused by liver X receptor activation is associated with insulin resistance in mice fed a high-fat diet

Abstract: Liver X receptors (LXR) are deemed as potential drug targets for atherosclerosis, whereas a role in adipose tissue expansion and its relation to insulin sensitivity remains unclear. To assess the metabolic effects of LXR activation by the dual LXRα/β agonist T0901317, C57BL/6 mice fed a high-fat diet (HFD) were treated with T0901317 (30 mg/kg once daily by intraperitoneal injection) for 3 weeks. Differentiated 3T3-L1 adipocytes were used for analysing the effect of T0901317 on glucose uptake. The following res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
3
3
0
Order By: Relevance
“…Activation of LXRs in mice by oral administration of a synthetic LXR agonist T0901317 led to a marked increase in SREBP-1 and lipogenic enzyme expression, as well as TG content in the liver [ 46 ]. In agreement with this study, another study reported that mice developed fatty liver in three weeks after the treatment with T0901317 by intraperitoneal injection under high-fat diet conditions [ 87 ]. Furthermore, global loss of LXRs in ob / ob mice impairs hepatic lipogenesis and reduces hepatic steatosis compared with control because of the decreased expression of SREBP-1 and lipogenic enzymes [ 88 ].…”
Section: Transcriptional Regulation Of Dnl In Adipocytessupporting
confidence: 87%
See 1 more Smart Citation
“…Activation of LXRs in mice by oral administration of a synthetic LXR agonist T0901317 led to a marked increase in SREBP-1 and lipogenic enzyme expression, as well as TG content in the liver [ 46 ]. In agreement with this study, another study reported that mice developed fatty liver in three weeks after the treatment with T0901317 by intraperitoneal injection under high-fat diet conditions [ 87 ]. Furthermore, global loss of LXRs in ob / ob mice impairs hepatic lipogenesis and reduces hepatic steatosis compared with control because of the decreased expression of SREBP-1 and lipogenic enzymes [ 88 ].…”
Section: Transcriptional Regulation Of Dnl In Adipocytessupporting
confidence: 87%
“…The underlying mechanism is probably that LXRα deficiency in fat impairs adipocyte lipolysis and fatty acid availability and oxidation [ 90 ]. Conversely, administration of LXRα agonist T0901317 in mice fed with a high-fat diet reduced fat mass, which was accompanied with increased adipocyte lipolysis and apoptosis, and decreased PPARγ transcriptional activity [ 87 ]. Although different mouse models and diets may contribute to the different effects of LXRs in ATs, these studies suggest that LXRs play a different role in adipocytes and hepatocytes.…”
Section: Transcriptional Regulation Of Dnl In Adipocytesmentioning
confidence: 99%
“…It has also been demonstrated that the activation of LXR-α impairs adipose expansion by increasing adipocyte apoptosis, lipolysis, and antagonizing the transcriptional activity mediated by PPAR-γ. This could contribute to a decrease in insulin sensitivity throughout the whole body [42]. These findings might explain what our study observed: that the LIR-MO individuals showed less expression of LXR-α in VAT in comparison with the HIR-MO individuals.…”
Section: Discussionsupporting
confidence: 54%
“…The allele associated with higher WHRadjBMI was associated with lower PRRX1, corresponding to more adipogenesis, and higher FMO1, corresponding to more storage of triglyceride in adipose 28,29 . The fourth gene detected using a secondary eQTL signal, SSR3, contributes to the formation of a vascular network in murine placenta 30 , and may reflect the blood component of adipose tissue; this GWAS signal colocalized with a primary eQTL for TIPARP, which positively regulates liver X receptor, which can impair adipose expansion 31 . While colocalized GWAS and eQTL signals do not provide causal mechanisms, they can suggest candidate genes for further investigation.…”
Section: Discussionmentioning
confidence: 99%